Effects of trunk posture on cardiovascular and autonomic nervous systems: A pilot study - Wang, Hao; Gao, Xiaolin; Shi, Yongjin; Wu, Dongzhe; Li, Chuangtao; Wang, Wendi (Frontiers in Physiology, 2022)
Objective: Although regular and moderate physical activity has been shown to improve the cardiovascular and autonomic nervous systems, little has been done to study the effects of postural changes in the movement on the heart and autonomic nervous system. To uncover changes in cardiac function and autonomic nerves induced by different underlying posture transitions and explore which trunk postures lead to chronic sympathetic activation. Therefore, this study investigated the effects of trunk posture on the cardiovascular and autonomic nervous systems. Methods: Twelve male subjects (age 24.7±1.3) underwent this study. The non-invasive cardiac output NICOM monitoring equipment and the FIRSTBEAT system are used to dynamically monitor seven trunk postures in the sitting position (neutral position, forward flexion position, posterior extension position, left flexion position, right flexion position, left rotation position, right rotation position) at the same time. Each posture was maintained for 3 minutes, and the interval between each movement was 3 minutes to ensure that each index returned to the baseline level. Repeated analysis of variance test was used to compare and analyze the differences in human cardiac function, heart rate variability index, and respiratory rate under different postures. Results: Compared with the related indicators of cardiac output in a neutral trunk position: the cardiac index (CI) was significantly reduced in forwarding flexion and left rotation (3.48±0.34vs3.21±0.50; 3.48±0.34vs3.21±0.46, ΔL/(min/m2)) (P=0.016, P=0.013), cardiac output (CO) decreased significantly (6.49±0.78vs5.93±0.90; 6.49±0.78vs6.00±0.96, ΔL/min)( P=0.006, P=0.014), the stroke volume (SV)decreased significantly (P=0.017, P=0.0003); heart rate (HR) increased significantly in posterior extension ; left rotation stroke volume index (SVI) decreased significantly (P=0.0003); in the analysis of HRV-related indicators, compared with the neutral trunk position, the LF/HF of the posterior extension was significantly increased , and the LF/HF of the forward flexion was significantly increased , and the frequency-domain index LF/HF of right rotation was significantly increased There was no significant difference in respiratory rate (P>0.05). Conclusion: A neutral trunk is the best resting position, and deviations from a neutral trunk position can affect the cardiovascular and autonomic nervous systems, resulting in decreased stroke volume, increased heart rate, and relative activation of sympathetic tone.